Political Opposition in the Early Turkish Republic : The Progressive Republican Party 1924-1925 - Zürcher, (Social, Economic and Political Studies of the Middle East and Asia ;, 1991)
The founding of the Progressive Republican Party in November 1924 marked the end of a power struggle within the Turkish nationalist movement. This struggle had been going on ever since the start of that movement in 1919 and had become acute after the establishment of the Turkish Republic in October 1923. The suppression of the party in 1925 marked the beginning of the period of one-party dictatorship which lasted until after the Second World War. This book describes the power struggles within the nationalist movement which gave birth to the party, its history, organization, power base, and ideological significance. A large number of important political documents from the period are presented in translation.